2010
DOI: 10.1080/07315724.2010.10719830
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Dietary Quality with the Aid of a Low Glycemic Index Diet in Asian Patients with Type 2 Diabetes Mellitus

Abstract: These results demonstrate the ability of low GI dietary advice to improve the dietary quality of Asian patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Thus, adding GI education to CHDR improved dietary fibre intakes in subjects which could not be achieved with CHDR. Such additional benefits in dietary quality when using low GI diets in the Asian population has also been documented earlier [56]. …”
Section: Discussionsupporting
confidence: 65%
“…Thus, adding GI education to CHDR improved dietary fibre intakes in subjects which could not be achieved with CHDR. Such additional benefits in dietary quality when using low GI diets in the Asian population has also been documented earlier [56]. …”
Section: Discussionsupporting
confidence: 65%
“…These studies consisted of 286,125 participants and 10,944 of these had Type II diabetes. A feeding trial of patients with Type II diabetes found that those on the diet of lower GI had a significant improvement in blood sugar status compared with those on the higher GI diet ([ Nisak et al 2010 ]), strongly suggesting that choice of carbohydrate will aid in the management of blood sugar status.…”
Section: Chronic Diseasesmentioning
confidence: 99%
“…Accordingly, acute experimental studies demonstrate a reduction in the postprandial glucose and insulin response to low GI compared with energy-matched high GI mixed meals (Galgani et al 2006; Stevenson et al 2009). Although low GI diets are commonly recommended to lower postprandial glycaemia (Buyken et al 2010), adherence to this type of diet can be poor (Nisak et al 2010). Furthermore, GI is not the single factor controlling postprandial glycaemia and there has been recent research interest in the potential impact of minimising prolonged periods of sitting during the postprandial period.…”
Section: Introductionmentioning
confidence: 99%